O ensino reflexivo da ortografia à luz da sociolinguística educacional - Santos, Thais Nunes Xavier dos (2019)
The present study has as object of study the teaching of orthography in a perspective guided by Educational Sociolinguistics. From the observation of the difficulties that students present in writing related to spelling and linguistic prejudice, it became necessary to develop a didactic intervention that softened the problems encountered. It is common to witness writing deviations in students' texts that relate to accentuation of words, exchanges of letters and difficulty in using the language in its varieties, recognizing the specificity of the genre in focus. Spelling, understood as a social convention, which is not subject to variation, occurs in a variety of ways, especially in the digital genres to which most students are connected most of the time. It is important to emphasize that spelling when not in accordance with the cultured norm may imply a series of consequences related to linguistic prejudice. Taking the didactic textbook as a guideline of the work of the teacher in the classroom, based on the National Curriculum Parameters, the teaching of spelling is not presented in a reflexive way and does not contemplate the linguistic and orthographic variation. Thus, according to the NCPs, Portuguese language teaching must be based on textual genres, observing its specificities such as style, content and compositional structure. In the search to soften the problems related to linguistic prejudice and to the concept of "Portuguese error", the research approaches strategies of teaching of spelling from these difficulties in writing, based on a proposal of work that values the linguistic variation, as well as the real uses of the language, according to Educational Sociolinguistics (BORTONI-RICARDO, 2004). Thus, the general objective of this research is to elaborate a didactic intervention centered on the teaching of orthography of the Portuguese Language through reflection and linguistic analysis, following the precepts of Educational Sociolinguistics. For that, workshops were developed as a method of work with varied themes, related to reflective teaching of spelling and applied in an eighth grade class. The workshops were elaborated from the analysis of the written language in the digital medium, as in WhatsApp messages and Facebook comments, which can be given formally or informally. The study describes the application of classroom intervention, showing that, in fact, the discussion about linguistic variation and what leads to linguistic prejudice is essential for the progress of studies and that spelling is a relevant content, which should be taught in all school years, capable of promoting very productive analyzes, awakening critical thinking about the uses of language.